2022
DOI: 10.1080/13504509.2022.2036855
|View full text |Cite
|
Sign up to set email alerts
|

Diaspora income, financial development and ecological footprint in Africa

Abstract: This study examines the impact of diaspora income on the ecological footprint of 22 countries African countries. Methodologically, we used the Driscoll-Kraay (1998) fixed-effect model, fixed effect instrumental variable regression, Machado and Silva (2019) panel quantile regression, and Dumitrescu and Hurlin (2012) causality test. There are four main important findings from this empirical study: (1) diaspora income has a negative and statistical impact on ecological degradation, (2) financial development plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
3
5
0
Order By: Relevance
“…This shows that FDV is consistent with environmental sustainability in Bangladesh. This outcome is parallel to the results obtained by Ramzan et al [ 78 ] for Pakistan, Arogundade et al [ 79 ] for Africa, and Ozturk et al [ 80 ] for South Asia, but contradicts the findings of Wang et al [ 81 ] for developing European countries. In practice, strengthening the financial system will help alleviate environmental challenges in Bangladesh.…”
Section: Resultssupporting
confidence: 78%
“…This shows that FDV is consistent with environmental sustainability in Bangladesh. This outcome is parallel to the results obtained by Ramzan et al [ 78 ] for Pakistan, Arogundade et al [ 79 ] for Africa, and Ozturk et al [ 80 ] for South Asia, but contradicts the findings of Wang et al [ 81 ] for developing European countries. In practice, strengthening the financial system will help alleviate environmental challenges in Bangladesh.…”
Section: Resultssupporting
confidence: 78%
“…(2021) also posited that the attainment of remittance-CO 2 emissions reduction targets is realizable through improved financial development. The above is consistent with Arogundade et al . (2022) who found a negative nexus in the moderation effect of financial development on the impact of remittances on CO 2 emissions.…”
Section: Introductionsupporting
confidence: 93%
“…Yang et al (2020) and Yang et al (2021) also posited that the attainment of remittance-CO 2 emissions reduction targets is realizable through improved financial development. The above is consistent with Arogundade et al (2022) who found a negative nexus in the moderation effect of financial development on the impact of remittances on CO 2 emissions. From the foregoing, it can be concluded that improved financial development is not only a necessary condition but a sufficient condition to attain external inflow-CO 2 emissions reduction targets.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations